Multiple Time Intervals of Visual Events Are Represented as Discrete Items in Working Memory - Fan, Zhiwei; Yotsumoto, Yuko (Frontiers in Psychology, 2018)
Previous studies on time perception and temporal memory have focused primarily on single time intervals; it is still unclear how multiple time intervals are perceived and maintained in working memory. In the present study, using Sternberg’s item recognition task, we compared the working memory of multiple items with different time intervals and visual textures, for sub- and supra-second ranges, and investigated the characteristics of working memory representation in the framework of the signal detection theory. In Experiments 1–3, gratings with different spatial frequencies and time intervals were sequentially presented as study items, followed by another grating as a probe. Participants determined whether the probe matched one of the study gratings, in either the temporal dimension or in the visual dimension. The results exhibited typical working memory characteristics such as the effects of memory load, serial position, and similarity between probe and study gratings, similarly, to the time intervals and visual textures. However, there were some differences between the two conditions. Specifically, the recency effect for time intervals was smaller, or even absent, as compared to that for visual textures. Further, as compared with visual textures, sub-second intervals were more likely to be judged as remembered in working memory. In addition, we found interactions between visual texture memory and time interval memory, and such visual–interval binding differed between sub- and supra-second ranges. Our results indicate that multiple time intervals are stored as discrete items in working memory, similarly, to visual texture memory, but the former might be more susceptible to decay than the latter. The differences in the binding between sub- and supra-second ranges imply that working memory for sub- and supra-second ranges may differ in the relatively higher decision stage.